PROFIL KESALAHAN PEMAHAMAN KONSEP CAHAYA PADA SISWA KELAS V SEKOLAH DASAR - Ela Suryani (Universitas Muria Kudus, 2018)
This research describes the error concept of light profile in grade V students of SD N Srondol Wetan 02. The error concept made by the students need to be analyzed further in order to get a clear and detailed description of the students' weaknesses in understanding the concept of light and used as a consideration of learning in the business improve the quality of the learning process. Subjects amounted to four students who error concept. Data collection techniques use documentation, tests, observations, and interviews. Analysis of qualitative data through three stages of data reduction, presenting data, and concluding. The results showed: (1) KP-1 students have low sample indicator but KP-2 students actually have good example indicator; 2) errors concepts occur in the concept of light sources, light-permeable objects, light refraction, light of light degradation, and objects utilizing the nature of light; (3) the factors causing error concept of students' are student only learning only the IPA textbook from the school and the notebook from the teacher, the student assumes that all the concepts derived from experience and natural phenomena are true without re-examining the correct theory, reasoning, incomplete and inaccurate reading of textbooks or problems of understanding, as well as the limitations of language in understanding the concept of light.